The Role of Lead Toxicity on Eruption Rate of Hypofunctional Incisors in Albino Wistar Rats - Javaid, Rashid; Mirza, Asad Javaid; Ahmed, Asrar; Ibrahim, Aqeel; Akhtar, Qayyum; Sana, Ruqayya; Rasul, Faiz (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES This objective of this study was to evaluate the role of a heavy metal- lead acetate in the eruption rate of hypo functional incisors in albino Wistar rats. METHODOLOGY An experimental study was done in animal house of Post Graduate Medical Institute, Lahore since March 2019 to March 2020. 34 adult albino Wistar rats were randomly divided into two groups (n=17 for each group) i.e., control and lead acetate group. Right mandibular incisors were selected for this study. Selected incisors were marked 1mm above the level of gingival papillae. The incisors were cut above this mark to make it hypo-functional. The readings were measured by digital Vernier caliper. This was considered as day 0. Incisors length was measured at day 0, 3, 6, 12 and 15 and eruption was calculated. The data was analyzed using SPSS version 22. RESULTS Eruption rate was similar throughout the study except last follow up. At the end of this study eruption of incisors in albino Wistar rats in control was 03.30±0.72mm, in lead 02.43±1.19mm. At day 15, the difference between control and lead group was statistically significant (p-value 0.033). CONCLUSION These results reveal that besides other causes of delayed tooth eruption excessive lead intoxication are also a causative factor of delayed tooth eruption.